Two-Phase Oil-Water Empirical Correlation Models for SCAL and Petrophysical Properties in Intermediate Wet Sandstone Reservoirs - Sabila, T.; Ben Mahmud, H.; Mahmud, W.; van Dijke, M. (IOP Publishing, 2019)
A consensus has long been established that the best secondary oil recovery through waterflood is attained in intermediate wet reservoir systems. In the absence of special core analysis (SCAL) data during the initial stages of field evaluation, experimentally-derived correlations are generated in this study for preliminary evaluation purposes. Currently, it is identified that ambiguity exists between petrophysical relationships in intermediate wet reservoirs. Clarifying these relationships provides us with further understanding into maximizing oil recovery in such systems. Hence, the main objective of this study is to analyse and provide further insights into the relationships between petrophysical properties, which are ultimately vital for reservoir simulations. The correlations are generated through linear regression analysis from experimental core measurements. It has been proven that the most reliable correlations are essentially empirical rather than theoretical, especially with the case of relative permeability. The variation of SCAL parameters and correlations generated are studied as a function of wettability, permeability, porosity, initial water saturation and rock type. It is observed that residual oil saturation is moderately correlated to Amott-Harvey wettability in an upward curvilinear relationship while scaled endpoint relative permeability in two-phase oil-water system is strongly and linearly correlated to wettability. When investigating the effects of permeability, one must take into account that having too low or too high value might present anomalies in the correlations. The general trend for intermediate wettability reservoir is that a higher permeability shows a shift towards less water-wet behaviour (shift to oil-wet). Moreover, for initial water saturation and wettability, the trend is towards more water-wet at higher initial water saturation. Meanwhile, porosity is not strongly correlated to any of the parameters except permeability.